خدمات الحجيج الصحيه الصحية في المملكة العربية السعودية في ضوء الوثائق البريطانية 1951- 195" - خليل حمود عثمان (مجلة كلية التربية, 2020)
This study showed the importance of health services that should be available in the seasons of Hajj, which tried the Saudi Arabian government make available service to pilgrims , knowing that those seasons are very important to the Saudis for they make such a financial revenues to the treasury of the kingdom . And with those migrant numbers from various regions of the world , the need for medical services fast to curb the spread of diseases transitional especially . Britain was closely monitoring what is going on inside Saudi territory , as the bodies of various diplomatic institutes , taken to monitor everything related to medical matters about the pilgrims of the house of God , brought to light a lot on arrivals from areas within the department of the British interest , noting the British cast doubt on maintaining the health of pilgrims and reduce the spread of diseases among them , and their ability to make available usual quarantine rooms for expatriates , moved the reports , for example , the United States to provide aid for pilgrims own . At the same time following activity of Malaysian Medical Mission traveling from Mecca and services provided to the pilgrims .